2020
DOI: 10.1111/gcb.15265
|View full text |Cite
|
Sign up to set email alerts
|

Half a century of Scots pine forest ecosystem monitoring reveals long‐term effects of atmospheric deposition and climate change

Abstract: At two forest sites in Germany (Pfaffenwinkel, Pustert) stocked with mature Scots pine (Pinus sylvestris L.), we investigated changes of topsoil chemistry during the recent 40 years by soil inventories conducted on replicated control plots of fertilization experiments, allowing a statistical analysis. Additionally, we monitored the nutritional status of both stands from 1964 until 2019 and quantified stand growth during the monitoring period by repeated stand inventories. Moreover, we monitored climate variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 66 publications
1
26
1
Order By: Relevance
“…The European studies that paid closest attention to C stocks in conjunction with acidification recovery found the opposite trends in C storage to ours, with a declining carbon pool in the Oa horizon [37]. This may be difficult to interpret as the European sites have a more complicated and longer history of manipulation [38].…”
Section: Comparison With Other Studiescontrasting
confidence: 70%
See 1 more Smart Citation
“…The European studies that paid closest attention to C stocks in conjunction with acidification recovery found the opposite trends in C storage to ours, with a declining carbon pool in the Oa horizon [37]. This may be difficult to interpret as the European sites have a more complicated and longer history of manipulation [38].…”
Section: Comparison With Other Studiescontrasting
confidence: 70%
“…They attributed this change to an inhibition of microbial activity and decomposition processes during higher acid loading. Similarly, in pine forests in Germany, Prietzel et al [38] in an unusually long study found that C stocks and base saturation decreased until about 2004 and then reversed showing signs of recovery in upper soil layers since then.…”
Section: Comparison With Other Studiesmentioning
confidence: 84%
“…The detection of growth disturbances improves with continuity of measurement on long-term experimental plots, e.g., using repeated surveys or permanent dendrometer records (Nehrbass-Ahles et al 2014;Prietzel et al 2020;Spiecker et al 2000). Thus, time series data should ideally be obtained over the entire tree lifetime of 100-200 years.…”
Section: Introductionmentioning
confidence: 99%
“…The most common objective of forest soil sampling, mainly from topsoil layers, is to provide reliable information about soil fertility and productivity [3], effects of forest management [4][5][6], and soil contamination with various substances [7][8][9][10][11][12]. Forest soils are also common objects of studies on water cycling, quality and retention [13,14], and carbon cycling and sequestration in relation to climate change [15][16][17]. Beside the unique scientific projects and problem-oriented inventories, large scale monitoring programs (i.e., on a regional, national, and continental scale) were launched to determine both the spatial and temporal trends in relation to environmental factors and human impacts [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Forest litter and mineral topsoil differ in their physical forms and are, thus, most commonly, separately sampled and analyzed, sometimes using different laboratory protocols [5,16,30,37,38,[42][43][44][45]. Alternatively, even in the contaminated sites, the litter layer is omitted and only the mineral topsoil is sampled and analyzed [7,9,11,27,32,34,39,46].…”
Section: Introductionmentioning
confidence: 99%